2021
DOI: 10.5005/jp-journals-10071-24019
|View full text |Cite
|
Sign up to set email alerts
|

iPad-based Apps to Facilitate Communication in Critically Ill Patients with Impaired Ability to Communicate: A Preclinical Analysis

Abstract: Background Inability to communicate is very distressing for patients in the intensive care unit (ICU). Most communication exchanges in ICU are initiated by healthcare workers (HCWs). Touch screen apps may enable patients to initiate communication and improve their interactions. Objectives This study aimed to evaluate the pertinent features of iPad-based apps designed for communication in ICU. Methods Apple “App Store” and Google “Play Store” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As a result, intubated patients can be well-being while intubated. 18,27,30 Unexpected for this study was that some patients' relatives saw the benefits of using digital communication technology through a tablet to help communicate needs, they would like to download an application to be packed into their own tablet for patients to use in cases where the patient is unable to remove the endotracheal tube and has a tracheostomy tube inserted and it is necessary to continue to communicate between patients and relatives at home. Previous studies support our study in that they found that family members are in need of a means to help communicate with patients when they visit them at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, intubated patients can be well-being while intubated. 18,27,30 Unexpected for this study was that some patients' relatives saw the benefits of using digital communication technology through a tablet to help communicate needs, they would like to download an application to be packed into their own tablet for patients to use in cases where the patient is unable to remove the endotracheal tube and has a tracheostomy tube inserted and it is necessary to continue to communicate between patients and relatives at home. Previous studies support our study in that they found that family members are in need of a means to help communicate with patients when they visit them at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Endotracheal intubation, tracheostomy, need for non-invasive positive pressure ventilation, head and neck surgery, stroke, sedation and sensory impairment, and different language are the common reasons for not being able to communicate, including with healthcare professionals. 1 Up to 40% of patients in the intensive care unit reported communication difficulties. 2 Another study this rate was 16-24%.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, personal protective equipment used in intensive care during the COVID-19 pandemic made communication difficult by blocking speech sounds and hiding lip movements and facial expressions. 1 During mechanical ventilation, patients temporarily lose their speech function because of intubation. Voiceless is a critical problem especially for patients who are conscious and connected to a ventilator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation